Abertura de capital das companhias estaduais de saneamento: uma análise a partir da experiência de Minas Gerais - Thiago Guedes de Oliveira (2015)
The work analyzes the initial public offering (IPO) of the Minas Gerais Sanitation Company shares in the stock market and its consequences, from data collected in official documents and databases, as well as field information gathered through semi-structured interviews with managers, technicians and experts involved in the area. To do this, it starts with a discussion about the contradiction between the authors who defend the organization of water supply and sewerage services based on economic efficiency criteria and those who support its subordination to the needs of the population. Using Joseph Stiglitz concepts and theories, it discusses market failures and the consequent need for state intervention in certain key sectors such as sanitation, although recognizes the inherent governments limitations. It describes the experiences of France, England and the Nordic countries, comparing them to the privatization models reproduced in Latin America. It presents the political, institutional and economic context that culminated in the IPO of the Company and identifies the main arguments used by supporters and opposed groups to this privatization strategy. Finally, it analyzes the impact of this change into the Companys management and the service provided by it. It concludes that Minas Gerais case does not differ from similar experiences that occurred throughout the world, because the arguments used to justify this operation has not been confirmed in the reality, the results were below expectations and the improvements identified cannot be attributed directly to the IPO. The current programs and activities of the Company are guided by market strategies, not always adjusted to the social interests. So it does not fulfill its role as a states instrument to implement public policies that aim to reduce the inequalities and increase the population welfare.